2010
DOI: 10.1186/1749-799x-5-76
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hip morphology between the sexes in patients undergoing hip resurfacing

Abstract: There is limited morphological data on the sex differences between the commonly used pelvic parameters. This study analysed the CT scans of 100 consecutive Caucasian patients, 61 males and 39 females, undergoing hip resurfacing arthroplasty surgery for hip osteoarthritis in one institution.There were no sex differences in femoral torsion/anteversion, femoral neck angle and acetabular inclination. Males had a mean femoral torsion/anteversion of 8 degrees (range -5 to 26 degrees), a mean femoral neck angle of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
4
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 18 publications
4
36
4
4
Order By: Relevance
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussioncontrasting
confidence: 54%
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussioncontrasting
confidence: 54%
“…Finally, Sankar and Flynn defined acetabular retroversion as an angle less than 0° [ 22]. Normal central acetabular version in the child is similar to that in the adult, with the literature reporting normal values from 8°to 20°, with typically any angle less than 10°considered retroverted [1,16,17,21]. Sankar and Flynn identified only one patient with severe retroversion (less than 0°), but perhaps other children with LCP disease with mild or moderate retroversion (0°to 10°) were considered to have normal version.…”
Section: Discussionmentioning
confidence: 86%
“…Staw biodrowy per se także cechuje się pewnym zróżnicowaniem płcio wym, choć wiedza na ten temat wymaga wciąż dowodów naukowych. W dotychczas przeprowadzonych badaniach stwierdzono, iż panewka żeńska w porównaniu z męską jest mniejsza i bardziej zwrócona ku przodowi, równocześnie gdy koniec bliższy kości udowej nie wykazuje istotnych różnic [4][5][6][7][8].…”
Section: Wstępunclassified
“…Różnice płciowe w jej ustawieniu mają znaczenie nie tylko w sensie antropometrycznym i antropologicznym, lecz mogą być kluczowe w prawidłowym osadzeniu elementu panewkowego endoprotezy cał kowitej stawu biodrowego, operacyjnym leczeniu kon fliktu panewkowo-udowego (FAI) czy przy planowaniu za biegów osteotomii w obrębie miednicy zmieniają -cych ustawienie i kształt panewki [4][5][6][7][8].…”
Section: Wstępunclassified
See 1 more Smart Citation